Ped-files a pediatric medical record system - Dy Tioco, Bimbo Bren U. (2007)
An Electronic Medical Record (EMR) System is an application that manages patient medical records in digital format. Its functions include storing of patient records, billing and accounting , and generating medical reports. A pediatric EMR does these, while also catering to the special needs of the pediatric practice like storing immunization records, keeping track of growth and development, and an ability to compare a child's vital signs and other physiologic parameters to age-based normal ranges. Most EMRs, however, are designed for adult-care only. These EMRs lack functions that are vital to pediatrics, and most of them are proprietary and require high costs. Because these proprietary EMRs are not open source, they cannot be modified to suit the needs of pediatrics. The Philippine pediatric community has not been able to utilize the advantages offered by EMRs, mainly because there is no pediatric EMR that conforms to Philippine health standards. This has forced pediatricians to stay with the paper-based record-keeping system and put up with its shortcomings, or use ERMs that are not designed for their practice. To solve this problem, this paper proposes Ped-O-Files, a portable, open source, easy to use, web-based EMR for Philippine pediatrics clinics. It will improve on the current situation of paper-based record keeping as well as assist on other clinical functions such as billing and accounting, patient scheduling, and doing medical reports. It will also conform to Philippine health standards as defined by the Philippine Pediatric Society (PPS), the governing body for Philippine pediatrics.